2012
DOI: 10.1007/s00228-012-1417-0
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties swallowing solid oral dosage forms in a general practice population: prevalence, causes, and relationship to dosage forms

Abstract: One in 11 primary care patients had frequent difficulties in swallowing tablets and capsules while GPs grossly underestimated these problems. Therefore, physicians should rule out swallowing difficulties regularly to avoid non-adherence and inappropriate drug modifications. Special attention should be paid to specific patient groups (e.g. women and patients with dysphagia, dysphagia indicators, or mental illness).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
245
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(263 citation statements)
references
References 40 publications
9
245
1
8
Order By: Relevance
“…Although the weights of the different formulations were found to vary slightly between formulations, there were no significant differences in the dimensions of the printed tablets (p> 0.05) ( Table 1). Tablets were designed in caplet shape to enhance patient compliance (Overgaard et al, 2001;Schiele et al, 2012). They were made of stacked 200 μm thick layers as it can be observed with SEM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the weights of the different formulations were found to vary slightly between formulations, there were no significant differences in the dimensions of the printed tablets (p> 0.05) ( Table 1). Tablets were designed in caplet shape to enhance patient compliance (Overgaard et al, 2001;Schiele et al, 2012). They were made of stacked 200 μm thick layers as it can be observed with SEM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Incidences of medication related swallowing difficulties might have contributed to these findings, as this a wellknown problem across all ages. A small number of studies investigating this issue in the general adult 205 population have reported prevalence rates between 9% to 40% (Marquis et al, 2013, DeRoche et al, 2003, Schiele et al, 2013. Remarkably, these studies have indicated a gender effect, with a significantly higher frequency of difficulties among females compared to males.…”
Section: Tablets and Capsulesmentioning
confidence: 98%
“…This study suggests that 10mm diameter 355 tablets would be unacceptable for around 40% of a general sample of children aged 6 to 11 years, while 13mm tablets would be unacceptable for nearly half of all adolescents. Research analysing reports of swallowing difficulties among adults suggest that this can arise when tablets are greater than approximately 8mm in diameter (Schiele et al, 2013, FDA, 2013. A review of all agreed PIPs by the end of 2011 found that tablets larger than 5mm had been approved for children aged 2 to 5 360 years and tablets larger than 10mm for children aged 6 to 11 years; studies assessing the effect of modifications were not included in the list of binding terms, and details of the therapeutic indications for these products were not included in the review (van Riet-Nales et al, 2014b).…”
Section: To Be White [Otherwise] I'd Feel Like I Was Takingmentioning
confidence: 99%
“…8,23 There is a clear need for the routine evaluation of patient's ODF requirements prior to the prescribing, dispensing and administration of medication. A previous quantitative systematic review called for the development and routine use of a validated screening tool to identify patients with difficulty swallowing medication.…”
Section: Complexitymentioning
confidence: 99%
“…7,8 There are a number of safety and efficacy concerns around modified medicines such as reduced dose accuracy, reduced drug stability and the potential to affect the pharmacokinetic and pharmacodynamic profile of the drug in vivo. [9][10][11][12][13][14] Guidelines advise that modifications should only be undertaken as a "last resort" 15 when "other methods have been considered".…”
Section: Introductionmentioning
confidence: 99%